Practical Analysis on the Reform of Chinese Interactive Teaching Mode Based on Cloud Computing and Random Forestry Model - Haoqiong Li (Forest Chemicals Review)
Cloud computing has been widely used and developed in industrial production and manufacturing. In this paper, cloud computing is used in Chinese interactive teaching, and the innovation model of Chinese teaching is studied. Random forest has fast operation speed and excellent performance in processing big data. Random forest is convenient to calculate the nonlinear effect of variables, and can reflect the interaction between variables. Under the guidance of the new curriculum reform, combined with the actual situation of front-line teaching, this study boldly tried the practice of interactive teaching in the actual Chinese teaching. This paper not only analyzes the shortcomings of traditional teaching, but also develops the advantages of traditional teaching on this basis to better serve the interactive teaching. This paper not only pays attention to the theory of interactive teaching, but also pays more attention to the effectiveness of interactive classroom, and uses successful cases to guide the teaching practice of Chinese new curriculum. The results show that the interactive teaching of Chinese is a bold practice of the new curriculum standard. It is a new education mode with rich content, far-reaching significance, challenging form, forward-looking consciousness and lasting effect on the basis of summarizing excellent traditional education experience and western education experience. Teachers’ correct understanding and effective practice of it is related to the integrity of students’ Chinese knowledge system and the comprehensiveness of their ability.